2020
DOI: 10.1061/(asce)ee.1943-7870.0001814
|View full text |Cite
|
Sign up to set email alerts
|

Potential Implications of Acid Mine Drainage and Wastewater Cotreatment on Solids Handling: A Review

Abstract: Acid mine drainage (AMD) is a persistent and extensive source of water pollution and ecological degradation. Co-treating municipal wastewater (MWW) with AMD using existing infrastructure at conventional wastewater treatment plants (WWTPs) may serve as a potential option for AMD abatement. However, commonly elevated iron and aluminum concentrations and low pH of AMD could negatively impact various processes at a WWTP. The focus of this mini-review was to determine how co-treating MWW with AMD could impact the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…However, as was highlighted in a recent review by Spellman, et al [36], various research studies have dealt with AMD-MWW co-treatment, but so far no study has dealt with the solids can are contained in the product sludge and have been generated during the interaction of AMD and MWW (co-treatment process). Therefore, in this work, apart from identifying the optimal conditions for AMD-MWW co-treatment, focus in also placed in the product sludge and specifically in identifying the fate and partitioning of inorganic contaminants post the cotreatment process.…”
Section: Introductionmentioning
confidence: 99%
“…However, as was highlighted in a recent review by Spellman, et al [36], various research studies have dealt with AMD-MWW co-treatment, but so far no study has dealt with the solids can are contained in the product sludge and have been generated during the interaction of AMD and MWW (co-treatment process). Therefore, in this work, apart from identifying the optimal conditions for AMD-MWW co-treatment, focus in also placed in the product sludge and specifically in identifying the fate and partitioning of inorganic contaminants post the cotreatment process.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the results of this study showed that groundwater from the study area was generally detrimentally affected by elevated levels of both major anions and cations as well as high EC as an indicator of salinity. The total hardness of the groundwater samples (Table 2) was generally >180 mg L −1 indicating significant groundwater hardness [38,39].…”
Section: Resultsmentioning
confidence: 99%
“…However, the recently introduced concepts of circular economy and ZLD in wastewater management necessitate the introduction of wastewater beneficiation, valorization, and reuse, with the co-treatment of different wastewater matrices being promising in this regard [6,15,16]. Specifically, the co-treatment of MWW with AMD has been found promising due to the P(MWW)-metals (AMD) scavenging mechanism [17]. Not only this, but struvite that has been recovered from MWW has also been used for the treatment of AMD [5].…”
Section: Introductionmentioning
confidence: 99%